2007
DOI: 10.3358/shokueishi.48.144
|View full text |Cite
|
Sign up to set email alerts
|

Determination Method for Ractopamine in Swine and Cattle Tissues Using LC/MS

Abstract: Simple and reliable methods using LC/MS have been developed for the determination of the b-agonist ractopamine in swine and cattle tissues. Ractopamine was extracted with ethyl acetate from muscle and liver, and the ethyl acetate layer was evaporated to dryness. The residue was purified by partition with acetonitrile/n-hexane. In the case of fat, ractopamine was extracted and purified by partition with acetonitrile/n-hexane. The resulting acetonitrile solutions were evaporated to dryness. The residue was disso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(7 citation statements)
references
References 14 publications
1
6
0
Order By: Relevance
“…In order to monitor the illegal use of ractopamine, it is necessary to develop proper residue detection methods in swine tissues, feeds, and urine. Recent researches have suggested instrumental methods to detect these residues (Sakai et al 2007;Shen et al 2007;Zhang et al 2009;Zhai et al 2011), but no mention of ractopamine-withdrawal period for finishing pigs were made. In this way, further studies are required to determine whether consumer safety can be assured without applying a ractopamine-withdrawal period.…”
Section: Ractopamine Residues In Animal Tissuesmentioning
confidence: 99%
“…In order to monitor the illegal use of ractopamine, it is necessary to develop proper residue detection methods in swine tissues, feeds, and urine. Recent researches have suggested instrumental methods to detect these residues (Sakai et al 2007;Shen et al 2007;Zhang et al 2009;Zhai et al 2011), but no mention of ractopamine-withdrawal period for finishing pigs were made. In this way, further studies are required to determine whether consumer safety can be assured without applying a ractopamine-withdrawal period.…”
Section: Ractopamine Residues In Animal Tissuesmentioning
confidence: 99%
“…Most of the studies available on RAC use growth performance traits (Aalhus et al, 1990;Barker et al, 2005;Ross et al, 2011) or carcass measurements, meat quality and sensory attributes (Fernández-Dueñas, 2008;Kutzler et al, 2011), but few studies have reported tissue residue concentrations (i.e., muscle and liver). Some studies have focused on comparing techniques to quantify residues (Shishani et al, 2003;Qiang et al, 2007;Sakai et al, 2007), but to our knowledge, there are no complete studies using RAC that reported live animal performance, carcass and meat characteristics, and residue concentrations in target tissues. Thus, the objective of this study was to investigate the effects of the addition of RAC plus amino acids on growth performance, carcass characteristics, cuts yield, meat quality, sensory attributes and residues in liver and muscle of finishing pigs.…”
Section: Introductionmentioning
confidence: 99%
“…Some studies do not use the step of hydrolysis with β-glucuronidase enzyme in the determination of RAC in tissues [14,[30][31][32]. In this work, we still reinforce the use of it, because RAC glucuronide metabolites A-F ( Fig.…”
Section: Extraction Methods and Lc-ms/ms Analysissupporting
confidence: 55%